A critical role of TRPM2 channel in Aβ42‐induced microglial activation and generation of tumor necrosis factor‐α. Issue 3 (16th November 2017) - Alawieyah Syed Mortadza, Sharifah; Sim, Joan A.; Neubrand, Veronika E.; Jiang, Lin‐Hua
Abstract: Amyloid β (Aβ)‐induced neuroinflammation plays an important part in Alzheimer's disease (AD). Emerging evidence supports a role for the transient receptor potential melastatin‐related 2 (TRPM2) channel in Aβ‐induced neuroinflammation, but how Aβ induces TRPM2 channel activation and this relates to neuroinflammation remained poorly understood. We investigated the mechanisms by which Aβ42 activates the TRPM2 channel in microglial cells and the relationships to microglial activation and generation of tumor necrosis factor‐α (TNF‐α), a key cytokine implicated in AD. Exposure to 10–300 nM Aβ42 induced concentration‐dependent microglial activation and generation of TNF‐α that were ablated by genetically deleting (TRPM2 knockout ;TRPM2‐KO) or pharmacologically inhibiting the TRPM2 channel, revealing a critical role of this channel in Aβ42 ‐induced microglial activation and generation of TNF‐α. Mechanistically, Aβ42 activated the TRPM2 channel via stimulating generation of reactive oxygen species (ROS) and activation of poly(ADPR) polymerase‐1 (PARP‐1). Aβ42 ‐induced generation of ROS and activation of PARP‐1 and TRPM2 channel were suppressed by inhibiting protein kinase C (PKC) and NADPH oxidases (NOX). Aβ42 ‐induced activation of PARP‐1 and TRPM2 channel was also reduced by inhibiting PYK2 and MEK/ERK. Aβ42 ‐induced activation of PARP‐1 was attenuated by TRPM2‐KO and moreover, the remaining PARP‐1 activity was eliminated by inhibiting PKC and NOX, but not PYK2 and MEK/ERK. Collectively, our results suggest that PKC/NOX‐mediated generation of ROS and subsequent activation of PARP‐1 play a role in Aβ42 ‐induced TRPM2 channel activation and TRPM2‐dependent activation of the PYK2/MEK/ERK signalling pathway acts as a positive feedback to further facilitate activation of PARP‐1 and TRPM2 channel. These findings provide novel insights into the mechanisms underlying Aβ‐induced AD‐related neuroinflammation. Main Points: TRPM2 channel is critical for Aβ42‐induced microglial activation and generation of TNF‐α. PKC/NOX‐mediated ROS generation and activation of the PYK2/MEK/ERK signaling pathway mediate Aβ42‐induced TRPM2 channel activation.